Unequal gender relations in the practices of girl marriage in poor families at East Java Province - Emy Susanti (Masyarakat, Kebudayaan dan Politik, 2018)
The practice of girl marriage in Indonesia is a social reality that has been going on from generation to generation. Although the average level of education in Indonesia is increasing and the government has limited the practice of child marriage, in some areas of East Java province the tendency of parents to marryoff their underage girls remains. This study aims to identify gender-based power relations within the practices of girl marriage in poor family in East Java province. This study is also aimed at revealing how the social reproduction of gender inequality values takes place in the girl marriage practices. This research was done by using qualitative method which was supported with quantitative data. This study shows that the victims of early marriage practices are girls. Gender-based-power relations between young wives with husbands, parents and in-laws are not equal. The unequal gender-based power relations in girl marriage practices in poor family are relate to limitation of knowledge and reproduce of power. The unequal gender relations are continuously reproduced through the imposition of negative social labeling on girls. The prevention of girl marriage requires a comprehensive approach by addressing the social and cultural values, especially promoting equal gender relations. One of the solutions is empowerment based on equal gender perspective.